Tailor-made chicken meat biscuits: optimizing functional properties with olive oil and flaxseed oil oleogels - Banisetty, Sonia; Mallika, E Naga; Rao, B Eswara; Rao, T. Srinivasa (Journal of Meat Science, 2024)
This study aimed to develop chicken meat biscuits incorporating oleogels derived from olive oil and flaxseed oil, using carnauba wax as the oleogelator. The objectives included standardizing the procedure for preparing chicken meat biscuits, developing oleogels, and evaluating the physico-chemical, microbiological, and sensory quality of the resulting products, along with determining shelf life. Chicken meat biscuits were formulated with commercial butter (C), olive oil oleogel (T1), and flaxseed oil oleogel (T2). Physico-chemical parameters, fatty acid profile, and sensory quality were analyzed. Stable oleogels were obtained, and chicken meat biscuits incorporated with flaxseed oil oleogel exhibited reduced hardness, increased baking yield and maintained proximate composition. Fatty acid profiling revealed a significant decrease in saturated fatty acids in T2, with an increased PUFA: SFA ratio and favourable health indices. Sensory evaluation indicated no significant differences among formulations. The selected T2 formulation underwent shelf-life assessment under ambient and refrigerated conditions. Shelf-life assessment showed T2’s superior performance in terms of pH, lipid peroxidation, microbial quality, and sensory acceptability over 45 days of storage. The findings suggest that these innovative biscuits have promising applications in the food industry, providing healthier alternatives without sacrificing taste and texture.